REPRESENTASI AHOK DALAM KASUS PENISTAAN AGAMA PADA SURAT KABAR BERDASARKAN ANALISIS SEMIOTIKA ROLAND BARTHES - I Gusti Ayu Rai; Adi Bayu Mahadian (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2017)
Jakarta governor candidate, known as Ahok tangled case of blasphemy, offensive surah Al-Maidah 51 during his campaign in the thousand islands. The case became a highlight public concern, especially among the Muslim community fatherly who considered him one insults the Islamic religion. These blasphemy cases reported by the mass media in Indonesia, some mass media reported Ahok case with the cartoon is the newspaper Suara Merdeka and Rakyat Merdeka. This study aims to determine the semiotic meaning of